Gut metagenome profile of the Nunavik Inuit youth is distinct from industrial and non-industrial counterparts - Abed, Jehane Y.; Godon, Thibaud; Mehdaoui, Fadwa; Plante, Pier-Luc; Boissinot, Maurice; Bergeron, Michel G.; Bélanger, Richard E.; Muckle, Gina; Poliakova, Natalia; Ayotte, Pierre; Corbeil, Jacques (Communications Biology, 2023)
Comparative metagenomics studies have highlighted differences in microbiome community structure among human populations over diverse lifestyles and environments. With their unique environmental and historical backgrounds, Nunavik Inuit have a distinctive gut microbiome with undocumented health-related implications. Using shotgun metagenomics, we explored the taxonomic and functional structure of the gut microbiome from 275 Nunavik Inuit ranging from 16 to 30-year-old. Whole-metagenome analyses revealed that Nunavik Inuit youths have a more diverse microbiome than their non-industrialized and industrialized counterparts. A comparison of k-mer content illustrated the uniqueness of the Nunavik gut microbiome. Short-chain fatty acids producing species, and carbohydrates degradation pathways dominated Inuit metagenomes. We identified a taxonomic and functional signature unique to the Nunavik gut microbiome contrasting with other populations using a random forest classifier. Here, we show that the Nunavik Inuit gut microbiome exhibits high diversity and a distinct community structure.